Design and Development of a Web-Based Laboratory Service System Using the Waterfall Method at SMKN 5 Padang - Fikri, Khairul; Adri, Muhammad; Irfan, Dedy; Syukhri (LITPAM, 2026)
The development of information technology has encouraged educational institutions to implement digital systems to improve the effectiveness and efficiency of administrative services. Laboratories in vocational schools play an important role in supporting practical learning activities; therefore, effective laboratory management is required to support operational activities and competency-based learning processes. However, laboratory management at SMKN 5 Padang was still conducted manually using notebooks and spreadsheet-based administration, causing several problems such as data inconsistency, scheduling conflicts, inefficient equipment borrowing processes, difficulties in monitoring inventory, and delays in report generation. This study aimed to design and develop a web-based laboratory service system at SMKN 5 Padang using the Waterfall software development model. The research stages consisted of requirement analysis, system design, implementation, verification, and maintenance. Data collection techniques included observation, interviews, and documentation studies involving laboratory staff, teachers, students, and school management. The developed system provides integrated features such as laboratory scheduling management, inventory management, equipment borrowing and returning services, damage reporting, and laboratory activity monitoring. The implementation results indicate that the proposed system successfully digitalizes laboratory administrative processes, improves data accessibility, simplifies operational workflows, and supports centralized laboratory management. Therefore, the developed system is expected to improve the effectiveness and efficiency of laboratory service activities at SMKN 5 Padang.